1992
DOI: 10.1172/jci115911
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production in host-versus-graft and graft-versus-host reactions in the rat.

Abstract: The present study was designed to determine whether *N 0 produced in vivo during the rejection of histoincompatible tissues might permit serum NOQ/N0 levels to serve as markers of a rejection reaction. Rat syngeneic and allogeneic liver, heart, bone marrow/spleen cell, small bowel, skin, and sponge matrix grafts were performed and the stable endproducts of N 0, NOQ/N0, were serially assayed in the serum of the grafted animals. A significant rise of serum NOQ/NO-levels in the allografted animals preceded the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(54 citation statements)
references
References 21 publications
0
53
1
Order By: Relevance
“…NO also inhibits the repair mechanisms of target tissue destruction by inhibiting proliferation of epithelial stem cells in the gut and skin (263). In humans and rats, the development of GVHD is preceded by an increase in serum levels of NO oxidation products (264)(265)(266)(267).…”
Section: Cellular Effectors-cytotoxic T Cells (Ctls) Are the Major Cementioning
confidence: 99%
“…NO also inhibits the repair mechanisms of target tissue destruction by inhibiting proliferation of epithelial stem cells in the gut and skin (263). In humans and rats, the development of GVHD is preceded by an increase in serum levels of NO oxidation products (264)(265)(266)(267).…”
Section: Cellular Effectors-cytotoxic T Cells (Ctls) Are the Major Cementioning
confidence: 99%
“…33 Nitrate and nitrite are the end products of nitric oxide breakdown in the blood and are an index of nitric oxide production. 34,35 Two rat cardiac allograft studies have shown increased plasma nitrate and nitrite during the early stages of rejection. 18,36 Urinary nitrate excretion has also been shown to increase eight-fold in untreated rejection compared to that seen in isografts.…”
Section: Acute Rejectionmentioning
confidence: 99%
“…Plasma nitrite levels and urinary nitrate excretion have been used as an index of NO production in vivo [14]. Langrehr et al have demonstrated that plasma nitrate levels increased in host-versus-graft and graft-versus-host responses in rats [13]. Wjnlaw et al have documented increased urinary nitrate excretion in cardiac allograft rejection in an experimental study [21].…”
Section: Introductionmentioning
confidence: 99%